Gestaltungsstrategien für den suburbanen Raum. Wissenschaftliche Annäherung an seine stadträumlichen Qualitäten und Potenziale. - Brandl, Anne; Barman-Krämer, Gabriela; Unruh, Patric (TH Zürich, NSL, 2007)
Das Forschungsprojekt basiert auf dem Forschungsansatz, Referenzbeispiele aus der Geschichte des Städtebaus für die Entwicklung von Gestaltungsstrategien für den suburbanen Raum hinzuziehen. Um auf der analytischen Ebene zu einer Bewertung der deskriptiv erfassten, städtebaulichen Eigenschaften suburbaner Räume gelangen zu können, stellen Referenzbeispiele eine mögliche Vergleichsebene dar. Im Sinne von Aldo Rossi wurde die Analogie als eine Methode herangezogen, mit der historische Erfahrungen dekontextualisiert und durch Abstraktion verfügbar gemacht werden können. Ergebnis der Verallgemeinerung sind sieben suburbane Städtebaukategorien: Knoten, Relikte, Siedlungsinseln, Restflächen, "Zerhäuselung", Transiträume und Superkomplexe. Beispielhaft zeigt diesen Prozess der Beitrag anhand der Erarbeitung der suburbanen Städtebaukategorie der "Siedlungsinsel". goj/difu

The research project "Design strategies for urban sprawl", developed at ETH Zurich, focused on a particular selection of urban design problems in suburban areas. Using the Glattal as a case study, a region north of the City of Zurich, the morphology and typology as well as visually perceptible formal attributes of suburban areas were investigated. The research goal was to establish a systematic design basis for the qualification suburban space in terms of urban design. To find potential solutions for the recorded deficiencies of suburban areas in terms of urban design, the project used the method of analogy. In doing so, the knowledge of how reference examples from the history of urban design have achieved spatial solutions became the main assumption to find helpful suggestions for comparable, to date unsolved, urban design problems in suburban areas. The focus of the examination of these historic examples therefore lay rather on their ability to translate the design strategies in terms of urban space than in the analysis of their particular attributes. The reference examples were decontextualized and abstracted in terms of urban design, which made them available for today's suburban space. By visualizing urban design strategies through collages and the superimposition of plans, images were generated that make potential qualities for urban space approachable on a sensual level and therefore initiate a discussion about appropriate as well as inappropriate urban design solutions for suburban space. difu
Keywords: Raumplanung; Stadtgestaltung; Stadtlandschaft; Kulturlandschaft; Suburbanisierung; Stadtregion; Stadtentwicklung; Stadtumland; Planungstheorie; Planungspraxis; Städtebau; Zwischenstadt; Vorstadt; Peripherie; Raumqualität; Eigenschaft; Gestaltung